Analysis of Glycerol in Nipa (Nypa fruticans Wurmb.) Kernel Extract (NKE) with High-Performance Liquid Chromatography (HPLC) Method - Mario Dario L. Berdolaga Jr. (Three E Science Institute, 2022)
The quantification of glycerol reveals application areas in research as well as industrial prospects for supplies of biodiesel. Although petroleum and fossil fuels are not sustainable sources of energy, these fuels are on the verge of being exhausted. The study aims to establish a novel, calibrated, simple, and accurate analysis of the glycerol content using High-Performance Liquid Chromatography (HPLC) method. The quantification of glycerol from Nipa Kernel Extract (NKE) using the HPLC method resulted from a 4.06% concentration using hydrolysis reaction with methanol and KOH catalyst. The pure and hydrolyzed NKE were monitored using isocratic elution with Hydrophilic-Interaction Chromatography (HPLC-HILIC). The chromatograms extracted from the LC were analyzed and validated and showed good performance in terms of linearity as implicated (R^2=0.9928), repeatability (%RSD range from 2.6758% and 16.6130%), intermediate precision (p-value (0.00119) <α), the limit of detection 0.0001458% (w/w), the limit of quantification 0.0004182% (w/w), and accuracy (76.7105% to 82.8505%) of hydrolyzed Nipa Kernel Extract (NKE). The results produced from the employed approach are sufficient for determining the concentration of glycerol, and the method itself can serve as an alternate way to conduct chemical analysis. Additional research revealed that the contaminants and free fatty acids connected to glycerol absorbed the same absorbance units. It is anticipated that the investigation and identification will include quantifying the concentration of other unknown compounds found in the matrix.